The micoostructure and optical properaties of black chromium coating on solar panel materials - 294082 Shalee Ramakrishnan (Skudai : Universiti Teknologi Malaysia, 2000)
Project Paper (Bachelor of Mechanical Engineering (Materials)) - Universiti Teknologi Malaysia, 2000